Shelter House Play Therapy for a Child With Autism - Azizi Yahaya; Irnawati Binti Haji Mahir; Gooh, Mo Lee; Ismail Maakip; Baharudin Mohd Arus; Peter Voo; Sharon Kwan Sam Mee (2018)
The aim of this present study is to identify the effectiveness of Shelter House Play Therapy towards the social responsiveness and social communication of children with autism in Brunei Darussalam. Instruments including Social Responsiveness Scale (SRS) and Social Communication Questionnaires (SCQ) were used to collect data from 27 respondents; 12 respondents were the experimental group and 15 respondents were the control group. It also incorporates the perception of parents and teachers towards the behaviour of their autistic children and students. Split-Plot ANOVA (SPANOVA) and Independent Sample T-test analyses were used to evaluate the treatment effectiveness of Shelter House Play Therapy towards the social responsiveness and social communication in autistic children. It was found that Shelter House Play Therapy has an impact towards the social responsiveness and social communication in children with autism, and there is a significant difference of social responsiveness and social communication between the experimental group and control group in terms of pre and post-test. These findings indicate the overall effectiveness of Shelter House Play.